Are health care assistants part of the long-term solution to the nursing workforce deficit in Kenya? - Louise Fitzgerald; David Gathara; Jacob McKnight; Jacinta Nzinga; Mike English (BMC, 2020)
Abstract This commentary article addresses a critical issue facing Kenya and other Low- and Middle-Income Countries (LMIC): how to remedy deficits in hospitals' nursing workforce. Would employing health care assistants (HCAs) provide a partial solution? This article first gives a brief introduction to the Kenyan context and then explores the development of workforce roles to support nurses in Europe to highlight the diversity of these roles. Our introduction pinpoints that pressures to maintain or restrict costs have led to a wide variety of formal and informal task shifting from nurses to some form of HCA in the EU with differences noted in issues of appropriate skill mix, training, accountability, and regulation of HCA. Next, we draw from a suite of recent studies in hospitals in Kenya which illustrate nursing practices in a highly pressurized context. The studies took place in neo-natal wards in Kenyan hospitals between 2015 and 2018 and in a system with no legal or regulatory basis for task shifting to HCAs. We proffer data on why and how nurses informally delegate tasks to others in the public sector and the decision-making processes of nurses and frame this evidence in the specific contextual conditions. In the conclusion, the paper aims to deepen the debates on developing human resources for health. We argue that despite the urgent pressures to address glaring workforce deficits in Kenya and other LMIC, caution needs to be exercised in implementing changes to nursing practices through the introduction of HCAs. The evidence from EU suggests that the rapid growth in the employment of HCA has created crucial issues which need addressing. These include clearly defining the scope of practice and developing the appropriate skill mix between nurses and HCAs to match the specific health system context. Moreover, we suggest efforts to develop and implement such roles should be carefully designed and rigorously evaluated to inform continuing policy development.